Principal Leadership Model in Improving the Quality of Education - Sugesti, Tutik; Siregar, Astri Novia; Tanjung, Bahdin Nur (Holistic Science, 2024)
This research aims to analyze various school principal leadership models that play a role in improving the quality of education through literature study. Principal leadership is recognized as a key factor in determining the quality and success of the educational process. This study examines literature related to instructional, transformational, visionary, participatory, and situational leadership models, and how the application of these models can contribute to improving the quality of education. The results of the literature review show that each leadership model has different strengths and weaknesses, and its effectiveness often depends on the specific context of the school. These findings also indicate that school principals who are able to integrate elements from various leadership models tend to be more successful in creating an educational environment that is oriented towards improving quality. This literature study provides theoretical insights that are useful for educational researchers and practitioners in developing effective leadership strategies to achieve goals in improving the quality of education.